Współpraca międzyregionalna w Europie na przykładzie województwa dolnośląskiego i Saksonii - Adamczuk, Franciszek (European Interregional Co-Operation : Lower Silesia and Saxony Case Study, 2007)
This study aims to introduce European interregional co-operation on the example of the union country of the Federal Republic of Germany - Saxony, and the Lower Silesian voivodship, named contractually Lower Silesia. The author has introduced all forms and areas of this co-operation in the context of being in force Saxony and Lower Silesia regional development strategies. Hereinafter one of the institutional forms of this co-operation, namely functioning since year 2000 The Saxony-Lower Silesian Workgroup, has I been analyzed. This study ends with, agreed on during the 2006 colloquium, list of development priorities and I the author's remarks on the circumstances of intensifying both regions' collaboration in the future.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 99-111